Testing for correctness of thermometers and pyrometers - Wallis, Robert Lynn (My University, 1892)
Introduction: Instruments for measuring the calorie condition of bodies are subject to a number of influences that tend to render their reading incorrect. Such as the irregular expansions of thermometer and pyrometer tubes and their containing fluid. The shrinking of the bulb after long use. The change of the molecular state under high temperatures. And the graduation of instruments too soon after they are made, not allowing them sufficient time to assume their final position. Mercury is generally employed as a means of estimating temperatures, as its coefficient of expansion remains constant for ordinary temperatures, but for very high temperatures it becomes unstable and boils at a point far too low to be employed in estimating the melting or boiling point of most metals. In such high temperatures it becomes necessary to employ a combination of metals generally steel and brass so arranged that they indicate temperature by a dial face and hand.
Testing for accuracy of thermometers and pyrometers
Citation: Wallis, Robert Lynn. Testing for correctness of thermometers and pyrometers. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Thermometer; Pyrometer; Mercury; Temperature; Engineering; Theses; Manuscripts (documents)